2017
DOI: 10.4236/ajcc.2017.63026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Trends and Land Cover/Use Dynamics within the Somone River Basin, Senegal

Abstract: This study was undertaken mainly to 1) investigate temporal trends in annual rainfall and temperature; 2) identify discontinuities in the time series; and 3) assess the Land Use/Land Cover Change (LULC) in the Somone coastal lagoon, within the river basin. The study examined temporal trends in rainfall (1931-2016) and temperature (1961-2016) datasets of Somone river basin, and breaks in time series using Mann-Kendall non-parametric test and other suitable statistical tools. Temporal evolution in LULC was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…LULC results in Somone have indicated a very dynamic area related to human pressures, exacerbated by climate change [90]. Thus, coastal lagoons are very dynamic and subject to constant changes, very sensitive and exposed to human pressures, with the development of urban and economic activities such as fishery, aquaculture and tourism [91].…”
Section: Land Use and Land Cover Changementioning
confidence: 99%
“…LULC results in Somone have indicated a very dynamic area related to human pressures, exacerbated by climate change [90]. Thus, coastal lagoons are very dynamic and subject to constant changes, very sensitive and exposed to human pressures, with the development of urban and economic activities such as fishery, aquaculture and tourism [91].…”
Section: Land Use and Land Cover Changementioning
confidence: 99%
“…A lot of studies on the effects of climate change had been done in various ecosystems such as climate variability in lakes [12] (Nzoiwu et al 2017), climate change impacts in crops and croplands in agro ecosystems [13] [14] as well as influence of climate change in land cover dynamics within the river basins which include mangrove, forest, beach, tidal areas, lagoon, river, settlements, barren salt areas and findings revealed that climate change is intensified by rapid urbanization in these ecosystems [14]. The current study did not in any way duplicate these earlier studies and would in fact use the results of recent studies including those cited above to validate the climate change risks and suitability of selected agri-aqua commodities as climate resilient livelihood options for selected communities in the country.…”
Section: Introductionmentioning
confidence: 99%